Assessment of Nutritional Status among the School-going Adolescents in a Rural Community of Bankura District, West Bengal: A Cross-sectional Study - Eashin Gazi; Amit Kumar Samanta; Arup Jyoti Rout; Tushar Kanti Saha (Journal of Medical Evidence)
Background: Adolescent is a very crucial period of life for the growth and development of the body and mind. Nutrition influences growth and development throughout infancy, childhood and adolescents. Aims and Objectives: The aim of the sudy was to assess the nutritional status in terms of thinness, overweight and obesity and stunting amongst the school-going adolescents and to find out the factors related to nutritional status amongst the study subjects. Methodology: Community-based descriptive cross-sectional study was conducted amongst six rural schools of Bankura-I community development block in Bankura district from July to September 2017. With the help of a pre-designed, pre-tested, semi-structured schedule, a total of 600 adolescent students were interviewed, and clinical examinations were done. The collected information was entered into Microsoft Excel sheet and analysed using SPSS-20. Results: The mean age of the study population was 13.2 ± 2.19 years. About one-third (32.8%) of adolescent students were thin, as per body mass index for age Z-score category. Normal nutritional status was found in the majority of students (63.8%), but overweight and obesity were only 3.4% amongst the adolescent students. Stunting (31.0%) was higher amongst the late adolescents, and also that the percentage of stunting was higher in adolescent girls (35.8%) than boys (15.0%). Stunting was also significantly related with caste, SE class, family type according to number of family members and birth order of study subjects. Conclusions: School-based as well as community-based adolescent-friendly health and nutrition education and services and economic development may improve the overall health and nutritional knowledge and status of adolescents.